Neurobiology and Genetics of Behavioural Syndromes of Alzheimer's Disease - McIlroy, Stephen; Craig, David (Current Alzheimer Research, 2004)
The number of people with cognitive impairment is rising in parallel with changing demographics. As health care budgets are coming under increasing strain with regard to the provision of nursing care, there is a substantial need for effective therapies which encompass greater understanding of the components of dementia that finally necessitate admission to residential or nursing home care. Behavioural and psychological symptoms of dementia (BPSD) are major independent risk factors for admission to institutional care and research into the origin of BPSD is gathering pace. In this review, we evaluate the neurobiological and genetic changes described in individuals with BPSD in Alzheimer's disease. Particular emphasis is placed on genetic theories of causation, namely that BPSD results directly or indirectly from known genetic risk factors for AD, or distinct genetic risk factors for psychiatric illness assume clinical significance within the degenerated Alzheimer's brain.
Keywords: Neurobiology